Atoms & molecules/ Physical Science in Action (gr 5-8) - Cardona, Tarquin; Palacio, Olga M.; Pospisil, Denise; Schlessinger, Andrew; Mitchell, Tracy; First Light Pictures; Schlessinger Media (Wynnewood, PA : Schlessinger Media, 2004)
Discusses how atoms bond to one another to form compounds and the three main subatomic particles--protons, neutrons, and electrons. Graphics, visuals, and a hands-on activity simulate the movement of atoms and molecules in different phases of matter.
Introduction -- The atom -- Electric charge -- Review #1 -- Elements -- The periodic table -- Chemical bonds -- Covalent bonding -- Ionic bonding -- Review #2 -- Phases of matter -- Investigation : movement of atoms.
Andrew Schlessinger and Tracy Mitchell, executive producers ; editors, Doug Tuero, Steve Sylvia ; on-line editors, Jeff Marino, Howard Silver ; original music, Jackie Thomas.
Denise Pospisil.
Grades 5-8.
DVD.
With English and Spanish language tracks ; closed-captioned.
Keywords: Atoms; Molecules; Video recordings for the hearing impaired; Educational films; Science films; Children's films